Computer Support to Teachers - Bhalla, Jyoti (Advances in Social Sciences Research Journal, 2015)
The potential of computer usage towards enhancing teaching learning process has received considerable attention in recent times. The computer support to teachers is a major issue around which discussions and researches about computer use seem to coalesce. The present study systematically and comprehensively assesses teachers’ perceptions regarding assistance available to teachers in schools in the use of computers in teaching-learning process i.e., administrators, experts, technicians, computer literate co-workers, colleagues, who endorse computer use. The findings suggest that overall, computer support to teachers is not provided always or on daily basis. As a consequence of implementation of favorable policies, schools occasionally provide support in use of computers. However, there is scope for further enhancement in provision of support to teachers related to allocation of more time to plan and integrate computers in curriculum, sufficient slots in the school time table for students to use computers for completing computer-based assignments, curriculum-related technology-coordinator, opportunities to discuss computer-related topics with colleagues and exchange ideas about ways of using computers in teaching-learning, and e-parental involvement. The findings emphasise that due consideration is required and significant efforts have to be made towards improving the computer support to desired levels in order to implement widespread adoption of computer use in teaching-learning process.